100 GSM paper as an SERS substrate for trace detection of pharmaceutical drugs in an aqueous medium. (22nd September 2022) - Sarma, Dipjyoti; Biswas, Sritam; Hatiboruah, Diganta; Chamuah, Nabadweep; Nath, Pabitra
Abstract: Surface-enhanced Raman spectroscopy (SERS) is a unique technique that allows us to detect samples in trace quantities. The spectral intensities of the characteristic Raman peaks of the analyte molecule are enhanced manifold in the presence of noble metal nanoparticles (NPs). The existence of NPs is necessary to couple the incident electromagnetic field with NPs through the localized surface plasmon resonance phenomenon, which primarily contributes to the enhancement of an SERS signal. The present work demonstrates the working of a paper-based SERS substrate to detect and quantify two pharmaceutical drugs—paracetamol and aspirin—in water. The proposed SERS substrate was obtained by drop-casting silver NPs over printing grade 100 grams per square meter (GSM) paper. 100 GSM denotes the class of paper where 100 grams of raw materials (cellulose) is used per square meter to manufacture the paper. The performance of the designed SERS substrate was initially evaluated with two Raman active samples—malachite green and rhodamine-6G. The applicability of the proposed SERS substrate was evaluated further through monitoring the Raman spectra of the two aforementioned pharmaceutical drugs in different field-collected water samples, thus establishing the reliability of the scheme in a real field environment.